Simultaneous Determination of Four Phenolic Acids in Terminalia by HPLC - Li, Xiaofen; Zhang, Gongxin; Zhou, Xuejin; Gao, Yuntao (Asian Journal of Chemistry, 2012)
A HPLC method is established for the simultaneous determination of four phenolic acids (gallic acid, vanillic acid, caffeic acid and p-coumaric acid) in the extract of Terminalia. XDB-C18 (4.6 × 150 mm i.d., 5 μm) column was used, the chromatography was carried out with a linear gradient program. The mobile phase was A: methanol and B: 1 % ethylic acid at flow rate of 1.0 mL min-1, the detection wavelength was 280 nm and column temperature was 25 ºC. The linear ranges were 80-800 mg/L for gallic acid, 2.5-250 mg/L for vanillic acid, 2.0-200 mg/L for caffeic acid and 1.0-100 mg/L for p-coumaric acid. The average recoveries (n=5) were 99.40 % with relative standard deviation (RSD) of 1.84 % for gallic acid, 98.5 % with RSD of 2.15 % for vanillic acid, 98.7 % with RSD of 1.90 % for caffeic acid and 99.3 % with RSD of 2.00 % for p-coumaric acid. These four phenolic acids were separated successfully from each other.